39 Molecular dissection of the impact of frequent genetic alterations on the response of head and neck cancers to anti-epidermal growth factor receptor-directed therapies. Issue 5 (May 2015) - Pogorzelski, M.; Ting, S.; Gauler, T.; Breitenbücher, F.; Vossebein, I.; Hoffarth, S.; Markowetz, J.; Lang, S.; Bergmann, C.; Brandau, S.; Abu-Jawad, J.; Schmid, K.W.; et al.
<x xml:space="preserve">Abstract</x> Introduction Monoclonal antibodies and tyrosine kinase inhibitors (TKI) targeting the EGFR are approved or under investigation for the systemic treatment of patients with HNSCC. However, primary and acquired resistance against EGFR-targeted therapies are frequently observed. Mutational activation of the EGFR signaling cascade as well as molecular changes caused by HPV infection are the most abundant oncogenic alterations in HNSCC. Against this background we have used preclinical cancer models to study the impact of activated PI3K/AKT and RAS/RAF/MAPK pathways or HPV16 oncoprotein expression on the response to anti-EGFR therapies. Materia and methods Cetuximab- and erlotinib-sensitive cancer cells were retrovirally transduced to express HPV16 oncoproteins E6 or E7, conditionally active AKT and RAF-1 or a RASG12V mutant. HPV16-positive cancer cells and cells harboring endogenously mutated PIK3CA or RAS were used as alternative models. Cell proliferation, induction of apoptosis, clonogenic survival and tumor growth in immune-compromised mice were analyzed in relation to treatment with anti-EGFR antibodies. In support, tumor samples from cetuximab-treated patients with recurrent or metastatic HNSCC were probed for p16INK4a expression, an established biomarker of HPV infection and retrospectively analyzed concerning the response rates (RR) and progression free survival (PFS) in relation to HPV status. Results Activation of the PI3K/AKT and the RAS/RAF/MAPK pathways strongly protected HNSCC cells against anti-EGFR therapies. Mechanistically, this resistance was mediated by changes in the expression of anti-apoptotic proteins and could be overcome by co-treatment with specific inhibitors of EGFR downstream signaling. In contrast, the endogenous HPV status of HNSCC cells or the expression of HPV oncogenes had no significant impact on cetuximab-mediated suppression of EGFR signaling and proliferation in vitro. In addition, response rates (45.5% versus 45.5%) and median progression-free survival (97 versus 92 days) following cetuximab-based therapy were similar in patients with p16INK4A-positive and p16INK4A-negative tumors. Conclusion Activation of the PI3K/AKT and the RAS/RAF/MAPK pathways functionally interfere with the activity of anti-EGFR therapies. In contrast, HPV status of HNSCC did not influence the response to cetuximab in our retrospective analyses and in our preclinical models. In conclusion, cetuximab treatment should be administered independently of HPV status.